Subcortical Deep Gray Matter Pathology in Patients with Multiple Sclerosis Is Associated with White Matter Lesion Burden and Atrophy but Not with Cortical Atrophy: A Diffusion Tensor MRI Study - Cappellani, R.; Bergsland, N.; Weinstock-Guttman, B.; Kennedy, C.; Carl, E.; Ramasamy, D.P.; Hagemeier, J.; Dwyer, M.G.; Patti, F.; Zivadinov, R. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: The association between subcortical deep gray matter, white matter, and cortical pathology is not well understood in MS. The aim of this study was to use DTI to investigate the subcortical deep gray matter alterations and their relationship with lesion burden, white matter, and cortical atrophy in patients with MS and healthy control patients. MATERIALS AND METHODS: A total of 210 patients with relapsing-remitting MS, 75 patients with progressive MS, and 110 healthy control patients were included in the study. DTI metrics in whole brain, normal-appearing white matter, normal-appearing gray matter, and subcortical deep gray matter structures were compared. The association between DTI metrics of the subcortical deep gray matter structures with lesion burden, normalized white matter volume, and normalized cortical volume was investigated. RESULTS: DTI measures were significantly different in whole brain, normal-appearing white matter, and normal-appearing gray matter among the groups (P < .01). Significant differences in DTI diffusivity of total subcortical deep gray matter, caudate, thalamus, and hippocampus (P < .001) were found. DTI diffusivity of total subcortical deep gray matter was significantly associated with normalized white matter volume (P < .001) and normalized cortical volume (P = .033) in healthy control patients. In both relapsing and progressive MS groups, the DTI subcortical deep gray matter measures were associated with the lesion burden and with normalized white matter volume (P < .001), but not with normalized cortical volume. CONCLUSIONS: These findings suggest that subcortical deep gray matter abnormalities are associated with white matter lesion burden and atrophy, whereas cortical atrophy is not associated with microstructural alterations of subcortical deep gray matter structures in patients with MS. ADaxial diffusivityFAfractional anisotropyHChealthy controlMDmean diffusivityPMSprogressive MSRDradial diffusivityRRMSrelapsing-remitting MSSDGMsubcortical deep gray matter